A new damage factor for seismic assessment of deficient bare and FRP-retrofitted RC structures. (1st December 2021) - Markou, George; Garcia, Reyes; Mourlas, Christos; Guadagnini, Maurizio; Pilakoutas, Kypros; Papadrakakis, Manolis
Highlights: A new 3D concrete material strategy when concrete is considered to be crushed. Damage factor to account cracking and rebar slippage under cyclic loading conditions. Validation by using experimental data on bare and FRP-retrofitted RC specimens. Capturing accumulated damage in concrete and steel according to the opening and closing of crack. 3D modeling is capturing extreme pinching on bare and FRP-retrofitted RC specimens. Abstract: The seismic assessment of reinforced concrete (RC) structures before and after retrofitting is a challenging task, mainly because existing numerical tools cannot accurately model the evolution of concrete damage. This article proposes an innovative numerical method suitable to model and assess the ultimate carrying capacity of RC structures. The modelling approach proposes a steel constitutive material model with a damage factor that accounts for accumulated damage within the surrounding concrete domain, which effectively captures bar slippage. The proposed method is validated with experimental results from full-scale cyclic tests on deficient bare and CFRP-retrofitted RC joints tested previously by the authors. The results indicate that the proposed simulation method captures the extreme nonlinearities observed in the tested RC joints, with acceptable accuracy and computational robustness. The results of this study are expected to contribute towards the development of more reliable numerical tools and design guidelines for efficient seismic assessment of RC structures before and after earthquakes.